No Moral Wiggle Room in an Experimental Corruption Game - Balafoutas, Loukas; Sandakov, Fedor; Zhuravleva, Tatyana (Frontiers in Psychology, 2021)
Recent experimental evidence reveals that information is often avoided by decision makers in order to create and exploit a so-called ‘moral wiggle room’, which reduces the psychological and moral costs associated with selfish behavior. Despite the relevance of this phenomenon for corrupt practices from both a legal and a moral point of view, it has hitherto never been examined in a corruption context. We test for information avoidance in a framed public procurement experiment, in which a public official receives bribes from two competing firms and often faces a tradeoff between maximizing bribes and citizen welfare. In a treatment where officials have the option to remain ignorant about the implications of their actions for citizens, we find practically no evidence of information avoidance. We discuss possible reasons for the absence of willful ignorance in our experiment.